2018
DOI: 10.26681/jote.2018.020305
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of an Interprofessional Geriatric Training Experience: Attitudes of Future Healthcare Providers

Abstract: As the older adult population increases, it is vital to educate and train healthcare providers as members of interprofessional healthcare teams who can work effectively with these individuals. Ageism is a potential obstacle to achieving this goal. The purpose of this pre/post-test design pilot study was to determine the impact of an interprofessional geriatric training experience on the attitudes of future healthcare providers towards interprofessionalism and working with older adults. Sixteen graduate level s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 13 publications
0
2
0
Order By: Relevance
“…Thus, it is important to educate and train health providers so that they can work effectively with patients from older age groups. Lisa et al reported that working experience with older people was valuable to get a better understanding of their problems (Knecht-Sabres et al, 2018). Furthermore, the emotional state of the health provider concerning elderly patients also contributes to the outcomes of care (Crespo et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, it is important to educate and train health providers so that they can work effectively with patients from older age groups. Lisa et al reported that working experience with older people was valuable to get a better understanding of their problems (Knecht-Sabres et al, 2018). Furthermore, the emotional state of the health provider concerning elderly patients also contributes to the outcomes of care (Crespo et al, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, not all HHWI have the same work experience, which has an impact on the pilgrims' health services. Almost all embarkations lacked health briefings and practical recommendations for dealing with elderly pilgrims, and some did not even provide any (Fahham et al, 2018;Ministry of Religious Affairs, 2013;Knecht-Sabres et al, 2018;Singka & Ericca, 2020).…”
Section: Introductionmentioning
confidence: 99%